Race does not predict skeletal‐related events and all‐cause mortality in men with castration‐resistant prostate cancer. Issue 14 (6th May 2020) - Patel, Devin N.; Howard, Lauren E.; De Hoedt, Amanda M.; Amling, Christopher L.; Aronson, William J.; Cooperberg, Matthew R.; Kane, Christopher J.; Klaassen, Zachary W.; Terris, Martha K.; Freedland, Stephen J.
Abstract : Background: The impact of race on prostate cancer skeletal‐related events (SREs) remains understudied. In the current study, the authors tested the impact of race on time to SREs and overall survival in men with newly diagnosed, bone metastatic castration‐resistant prostate cancer (mCRPC). Methods: The authors performed a retrospective study of patients from 8 Veterans Affairs hospitals who were newly diagnosed with bone mCRPC in the year 2000 or later. SREs comprised pathologic fracture, spinal cord compression, radiotherapy to the bone, or surgery to the bone. Time from diagnosis of bone mCRPC to SREs and overall mortality was estimated using the Kaplan‐Meier method. Cox models tested the association between race and SREs and overall mortality. Results: Of 837 patients with bone mCRPC, 232 patients (28%) were black and 605 (72%) were nonblack. At the time of diagnosis of bone mCRPC, black men were found to be more likely to have more bone metastases compared with nonblack men (29% vs 19% with ≥10 bone metastases; P  = .021) and to have higher prostate‐specific antigen (41.7 ng/mL vs 29.2 ng/mL; P  = .005) and a longer time from the diagnosis of CRPC to metastasis (17.9 months vs 14.3 months; P  < .01). On multivariable analysis, there were no differences noted with regard to SRE risk (hazard ratio [HR], 0.80; 95% CI, 0.59‐1.07) or overall mortality (HR, 0.87; 95% CI, 0.73‐1.04) between black and nonblack people, although the HRs were <1, which suggested the possibility of better outcomes. Conclusions: No significant association between black race and risk of SREs and overall mortality was observed in the current study. These data have suggested that efforts to understand the basis for the excess risk of aggressive prostate cancer in black men should focus on cancer development and progression in individuals with early‐stage disease. Abstract : The impact of race on the outcomes of patients with advanced prostate cancer is controversial. Among men with advanced prostate cancer, the authors report no significant association between black race and the risk of skeletal‐related events and overall mortality.